Philosophy of Science as a Foundation for Scientific Method Development - M. Thontawi; Ahmad Syukri SS; Badarussyamsi (Darul Ilmi Bina Insan Foundation, 2024)
Philosophy of science plays a critical role as the epistemological foundation in shaping research methodologies and guiding scientific inquiries. Although previous literature emphasizes the theoretical connection between philosophy and science, studies synthesizing how specific philosophical paradigms directly dictate operational research designs remain limited. This study aims to analyze the role of philosophy of science in developing scientific methods through a critical synthesis of ontological, epistemological, and axiological pillars across major research paradigms. Utilizing a descriptive-analytical library research approach, relevant literature on philosophy, methodology, and scientific inquiry was systematically examined. The findings demonstrate that philosophical paradigms directly govern research operations: (1) positivism enforces quantitative, experimental designs aimed at empirical verification and causal relationships; (2) constructivism drives qualitative, naturalistic approaches focused on contextual meaning and dialectical interpretation; and (3) pragmatism serves as the theoretical bridge for mixed-methods research, prioritizing practical problem-solving over methodological purity. Furthermore, the study underscores that integrating axiological reflection is vital for navigating contemporary methodological challenges, including algorithmic bias and data ethics. In conclusion, philosophy of science provides both the logical structure for operational methodology and the ethical framework necessary for maintaining scientific integrity